Correlates of Reading Habits and Academic Performance of Grade 4 Pupils in a Public School - Frame Jane A. Mendaros (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study was conducted to analyze the correlates of reading habits and academic performance of Grade IV pupils in a public school, school year 2022-2023. The study focus only on the reading habits of pupils and academic performance of pupils at home and in the school. There will be fifty nine total population of Grade IV pupil-respondents of Liozon Elementary School, Palauig, Zambales. The researcher will use survey questionnaire to gather data needed in the study, such as profile of respondents, Contributory Factors Affecting Reading Proficiency, Reading Proficiency Level of the pupils, and Average Academic Performance in English. The data gathered will be checked, tallied and treated using appropriate statistical tools such as frequency, percentage, mean, and Chi- Square. Treated data will be presented through tables and graphs, it will be analyzed and interpreted. Interpreted data will be summarized, concluded, and recommended for future research study. The result would be the reading proficiency level of the pupils is dependent on the average academic performance in English. Based on the findings, there is a significant correlation between the reading habits and the academic performance of pupil-respondents in English.